Factor Affecting Knowledge Transfer Successfulness of Digital Tools: A Case Study of Petrochemicals Company in Thailand - Sakasuppharurk, Fariya; Khongmalai, Orapan (Suan Dusit Graduate School Academic Journal, 2024)
This quantitative research aimed to study the component of factors affecting the success of digital knowledge transfer for digital competency enhancement of Non-IT employee and provide ways to develop strategies for transferring digital knowledge in the organization. The 442 samples of a petrochemical company in Thailand were randomly selected by purposive sampling method. The data collection was conducted via online closed-ended questionnaire with the testing of content validity and reliability. The data were analyzed using exploratory component analysis techniques to define complementary factors and regroup factors. The results of the research revealed that the factors affecting the success of digital knowledge transfer consisted of 5 factors; namely, (1) Knowledge Transferor, (2) Knowledge Receiver including knowledge, experience, absorptive capacity and willingness, (3) Technology Characteristic, (4) Transfer Process (5) Digital Culture. Regarding the ways to develop strategies, the organization should focus all 5 factors; disseminative capacity of transferor, willingness building of receiver for digital adoption, selection suitable and easy-to-use digital tools, development of the knowledge transfer focusing a content and practice process and continuously organization supporting in term of resources, top management and communication.